Design of the Savings and Loan Accounting Information System for Sumber Bahagia Savings and Loan Cooperative Utilizing The CodeIgniter Framework - Yulianto, Hery Dwi; Wahyudi, Rizmya Bunga (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2024)
This research focuses on analyzing and designing an accounting information system aimed at managing savings and loan transactions at the Sumber Bahagia Savings and Loan Cooperative. The cooperative currently faces challenges in transaction recording, including reliance on applications like Microsoft Excel, inefficiencies in data storage, transaction management, and financial report preparation. These limitations often result in data discrepancies, errors, and delays in generating accurate financial information. Therefore, an integrated accounting information system is essential to address these issues effectively. The methodology employed by the researcher is the descriptive method, which seeks to provide an overview of the current system and propose a more effective solution through stages of data collection, analysis, design, system development, application creation, and system testing. The analysis phase includes developing data flow diagrams, flowcharts, account data coding, normalization, and relationship diagrams to ensure a clear understanding of data processes and their interrelations. The system development process involves building a robust database structure and creating a web-based application using the CodeIgniter framework, ensuring scalability, reliability, and user accessibility. The output design aligns with current accounting standards, addressing essential functions such as transaction recording, journal posting, ledger creation, trial balance preparation, and profit calculation reports. By implementing this system, the cooperative is expected to improve efficiency, accuracy, and transparency in financial operations. Additionally, the system facilitates the auditing of financial records and enhances decision-making processes by providing timely and reliable financial reports. This research contributes to understanding how accounting systems support financial management in cooperatives.